THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON COMPANY VALUE IS MODERATE BY COMPANY TRANSPARENCY - Ismail Badollahi; Wahyuni , Wahyuni; Marya Ulfa (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this study is to determine the influence of corporate social responsibility disclosure on corporate value, with corporate transparency as a moderating variable. This research is quantitative in nature, employing a descriptive approach. The population of this study comprises all manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2022, with a sample size of 240 financial data from various companies. The data source utilized is secondary data obtained from official documents on the Indonesia Stock Exchange website. The data analysis model employed is moderated regression analysis (MRA), processed using the statistical software SPSS. The research findings indicate that (1) corporate social responsibility disclosure has a positive and significant impact on corporate value in manufacturing companies listed on the Indonesia Stock Exchange, and (2) corporate social responsibility disclosure has a positive and significant impact on corporate value through transparency as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange.